Current meter velocities form mooring AURORA1 recovered during RV POLARSTERN cruise PS137 - Maren Walter; Joel Bracamontes Ramirez; Jonathan Mette (PANGAEA, 2025)
This dataset contains time series of current velocities in North-South and East-West components measured by four Aanderaa Doppler Current Meter RCM11 at different depths as part of the mooring AURORA1. (Other parameters measured with this mooring will be published separately). The mooring was deployed during the cruise PS121 at 2022-07-05 and recovered during the RV POLARSTERN cruise PS137 at 2023-07-02 (approximately one year). Measurements were taken at intervals of one hour. The mooring was deployed at the Aurora hydrothermal vent field in the Gakkel Ridge rift valley in the Eurasian Basin of the Arctic Ocean at approximately -6 degrees longitude and 82 degrees latitude. The aim was to measure the local velocity field and consequently to investigate its influence on the dispersal of fluids emitted by the hydrothermal vent field. The data was measured by an acoustic doppler current meter. Binary values were exported from the devices and scaled to the instrument extquotesingles resolution range. Gaps in the timestamp data were filled by linear interpolation.